2007
DOI: 10.1002/anie.200703397
|View full text |Cite
|
Sign up to set email alerts
|

A Genetically Encoded Bidentate, Metal‐Binding Amino Acid

Abstract: A two‐ring binder: To facilitate the design of metalloproteins, the bidentate, metal‐binding amino acid bipyridylalanine (BpyAla) was genetically encoded in E. coli in response to the amber nonsense codon with high fidelity and yield. The incorporation of BpyAla requires a BpyAla‐specific aminoacyl‐tRNA synthetase, which was evolved in a stepwise fashion. The structural basis of selective recognition of BpyAla by this synthetase was also determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
119
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(119 citation statements)
references
References 31 publications
0
119
0
Order By: Relevance
“…The crystal structure of BpyRS complexed with Bpy-Ala showed that the amino acid binding site could accommodate the extra two carbons of Phen-Ala (Figure 2). 10 The structure also showed that the two pyridine rings in Bpy-Ala are not on the same plan; one of the rings was twisted at 21 degree, while the Phen ring has a planar structure. However, we expected that BpyRS might still recognize and aminoacylate Phen-Ala to the corresponding tRNA.…”
Section: Resultsmentioning
confidence: 98%
“…The crystal structure of BpyRS complexed with Bpy-Ala showed that the amino acid binding site could accommodate the extra two carbons of Phen-Ala (Figure 2). 10 The structure also showed that the two pyridine rings in Bpy-Ala are not on the same plan; one of the rings was twisted at 21 degree, while the Phen ring has a planar structure. However, we expected that BpyRS might still recognize and aminoacylate Phen-Ala to the corresponding tRNA.…”
Section: Resultsmentioning
confidence: 98%
“…2 (37)) and (2,2′-bipyridin-5-yl)alanine ( Fig. 2 (38)), can be readily incorporated into proteins in E. coli [121,122]. Heavy metal cations can be loaded, and their scattering may also be used to solve the phase.…”
Section: Applications In X-ray Crystallographymentioning
confidence: 99%
“…This has allowed structure and multimer formation of Cu(I)-binding proteins to be explored, as the nitroxide interactions are not influenced by the presence of diamagnetic Cu(I) [31]. Introduction of paramagnetic copper sites into proteins has utilized genetically encoded artificial ligands [36], sitedirected mutation to introduce histidine residues [33] or the incorporation of sequences known to coordinate Cu(II) [34,35]. The addition of sequences based on copper sites from the prion protein (viz.…”
Section: Paramagnetic Copper and Nitroxide Spin-labelsmentioning
confidence: 99%